Who are the loss-averse farmers? Experimental evidence from structurally estimated risk preferences. (30th September 2022) - Bonjean, Isabelle
Abstract: Even though recognised to be of increasing importance, robust estimations of European farmers' risk preferences are still scarce. Using an incentivised lab-in-the-field experiment with farmers, free of learning bias, this paper analyses the structurally derived parameters of risk preferences based on the cumulative prospect theory. The sector studied is the apple and pear sector in Flanders, Belgium. Farmers are found to be highly risk-averse and to distort probabilities by overweighting a small probability of desirable outcomes. However, there is no evidence of loss aversion on average, unlike previous studies. Moreover, investigating the heterogeneous effects shows that some farmers significantly differ from the representative agent by still being extremely loss-averse. The results of this piece of research prove the need to consider heterogeneity within and across sectors when assessing farmers' risk preferences.